MICROBIOLOGICAL CHARACTERISTICS OF MEAT OF SIRI BENEFITED IN ANTONINA (PR) BEFORE AND AFTER THE ADOPTION OF GOOD MEASURES OF PRACTICAL - Vieira, Denise Maria; Naumann, Carlos Roberto Conti; Ichikawa, Takaaki; Cândido, Lys Mary Bileski (Scientia Agraria, 2006)
The crab meat that is produced in Antonina (PR) is traditionally processed and commercialized informally under conditions that are many times precarious. With the Serramar Processing Unit a new model of industrial processing is sought. The adoption of of good manufacturing practices is made necessary to assure quality and safety of the foods. The main goal of this work is to assess the quality of the product by microbiologic analyses, considering the adoption of measures of good manufacturing practices. The microbiologic analysis of the supplied water and the crabmeat processed in the unit was used as an assessing tool. The crab meat samples were distributed in four groups: group I – before the alteration made in the hygiene process of the objects, tools and hands, exposure time of the crab meat to room temperature and the use of gloves; group II – after the adoption of good manufacturing practices for the hygiene process of objects, tools and hands; group III – after the adoption of the hygiene process together with the diminishing of the crab meat exposure time to room temperature and group IV – after the adoption of hygiene measures, diminishing of exposure time and the use of gloves. The supplied water did not present any microbiological growth. The crab meat presented the following results after the analyses: contamination by mesophylic and high total coliform MPN (most probable number), higher in group I and then going down as good practice measures were being adopted. The thermal-tolerant coliform MPN were high in group I, diminishing in the following groups showing an unexpected growth in the group IV. Such growth could be related to seawater contamination and inappropriate cooking. In all samples the presence of Salmonela sp was negative. The search for Staphylococus aureus showed itself in disagreement with the current regulations in the first three groups and within regulation limits in the group IV. For the processing of the crab meat the adoption of hygiene procedures and the diminishing of exposure time had showed themselves insufficient to prevent the growth of S. aureus. The use of gloves is made necessary. The results presented reinforce the need for the adoption of good manufacturing practices. There is a need for training and staff’s professional upgrading as well as the monitoring of seawater quality and appropriate sanitary-hygienic conditions. Such measures should be included in the good manufacturing practices manual.